Fire Risk Vulnerability in Informal Settlements: The Case of Ashaiman - Sarpong, A.O. (University of Ghana, 2013)
Ghana, like most developing countries is undergoing rapid urbanization. This rapid increase in the urban population has exerted severe pressure on most cities‟ limited infrastructure, the consequence of which includes the mushrooming of informal and slum communities. In the main, most dwellers in these settlements have become vulnerable to a wide range of disaster risks particularly fire hazards largely because of the poorly constructed makeshift dwellings. The study was concerned with the level of fire risk vulnerabilities within one such community - Ashaiman, one of the biggest informal settlements in Ghana, and identifies some coping strategies the residents employ to mitigate their conditions. The study employed multiple research methodologies - structured household questionnaire, key informant interviews, focus group discussions, direct observations, the use of the GPS and the analysis of results using the Pearson‟s Chi-square test - in pursuance of the objectives set. The findings have revealed that illegal connection of electricity for domestic and commercial purposes is a major cause of fire incidence in the community which also has its antecedent to a state policy that does not permit the connection of the national grid to “illegal structures”. The situation has been exacerbated by the use of wooden planks in construction. The non-existence of fire hydrants within the research localities was also identified and highlighted. In the midst of their current circumstances, many residents resort to relying on the benevolence of their relatives, friends, the community as well as ethnic associations among other non- governmental and community-based/faith-organizations to hold back some of their predicaments emanating from the incessant fire incidences. Others have also ingeniously resorted to the use of sand to douse out fires. The study recommends regularization and on-site redevelopment of the settlement as part of the measures to address the current situation.
Thesis (MPHIL) - University of Ghana, 2013